1996
DOI: 10.1063/1.360932
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of nitrogen doped p-gallium selenide single crystals

Abstract: Nitrogen doped gallium selenide single crystals are studied through Hall effect and photoluminescence measurements in the temperature ranges from 150 to 700 K and from 30 to 45 K, respectively. The doping effect of nitrogen is established and room temperature resistivities as low as 20 ⍀ cm are measured. The temperature dependence of the hole concentration can be explained through a single acceptor-single donor model, the acceptor ionization energy being 210 meV, with a very low compensation rate. The high qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…We also carried out temperature dependent resistivity measurement for unimplanted and annealed sample at 500 °C and no appreciable change in resistivity was observed for the sample A0. As seen from Table 1, doping with nitrogen by ion implantation reduced the resistivity of GaSe single crystal five orders of magnitudes; this result suggests the effect of N-induced modification and doping of GaSe single crystal and the resistivity values obtained in this study are consistent with what was observed by chemical doping technique [8].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We also carried out temperature dependent resistivity measurement for unimplanted and annealed sample at 500 °C and no appreciable change in resistivity was observed for the sample A0. As seen from Table 1, doping with nitrogen by ion implantation reduced the resistivity of GaSe single crystal five orders of magnitudes; this result suggests the effect of N-induced modification and doping of GaSe single crystal and the resistivity values obtained in this study are consistent with what was observed by chemical doping technique [8].…”
Section: Resultssupporting
confidence: 93%
“…Using Bridgman systems, GaSe single crystals doped with different elements from different group by adding the impurities to the growth ampoule are produced and studied by various researchers [5,6,7,8]. It is quite hard to control the amount of impurity in the method of adding the impurities to the ampoules due to segregation and solubility problems.…”
Section: Introductionmentioning
confidence: 99%
“…Although the structural, electrical, optical absorption and photoelectric properties have been widely investigated [6][7][8][9][10], only a few reports have been published on the metal/p-GaSe SBDs [11][12][13][14][15][16]. In contrast to other layered semiconductors [17][18][19][20][21], to my knowledge, measurements and modelling of the characteristic parameters for silver SBDs fabricated on p-GaSe have not yet 0925-8388/$ -see front matter © 2010 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the investigations about the optical and electrical properties have been made on chemically doped crystals [4][5][6][7]. It is difficult to control the amount of impurity in the method of adding the impurities to the ampoules due to segregation and solubility problems.…”
Section: Introductionmentioning
confidence: 99%